Pengaruh Persepsi Harga dan Citra Merek Terhadap Keputusan Pembelian Melalui Minat Beli Sebagai Variabel Intervening Pada Dealer Suzuki Motorcycle di Palangka Raya - Riza Rivandy; Salbeta Sihombing; Kheizia Wulandari; Petra Simbolon; Andrey Anggiat Imanuel Simanjuntak; Frederick Nicholas Perangin Angin; Raymundus Alfredo Kristanto (CV. ITTC INDONESIA, 2025)
The automotive industry in Indonesia is experiencing rapid growth, especially in the motorcycle segment which is the main choice of the community. However, the high market potential is accompanied by challenges such as brand competition, changes in consumer preferences, and government regulations. This study aims to analyze the effect of price and brand image on purchasing decisions with purchase intention as an intermediary variable, a case study at a Suzuki motorcycle dealer in Palangka Raya. The method used is qualitative-associative with a causality approach. Primary data were collected through an online questionnaire to Suzuki motorcycle users, while secondary data were obtained from literature and other relevant sources. Data analysis was carried out using the Partial Least Square (PLS) method with the help of SmartPLS software. Based on the study, it can be seen that purchase intention has a significant positive impact from price perception and brand image. In addition, purchase decisions have a significant positive impact from purchase intention. However, both brand image and price perception have an indirect impact on purchasing decisions through the intermediary variable of purchase intention, not directly. Based on these results, Suzuki should focus its marketing efforts on increasing consumer interest in making purchases, especially by strengthening its reputation and offering competitive prices.